# S-n-1-6-n-n-1-2n-1-1-show-that-S-converges-2-give-the-value-of-S-

Question Number 131428 by pticantor last updated on 04/Feb/21
$$\:\boldsymbol{{S}}=\underset{\boldsymbol{{n}}\geqslant\mathrm{1}} {\sum}\frac{\mathrm{6}}{\boldsymbol{{n}}\left(\boldsymbol{{n}}+\mathrm{1}\right)\left(\mathrm{2}\boldsymbol{{n}}+\mathrm{1}\right)} \\$$$$\left.\mathrm{1}\right)\:\boldsymbol{{show}}\:\boldsymbol{{that}}\:\boldsymbol{{S}}\:\boldsymbol{{converges}} \\$$$$\left.\mathrm{2}\right)\:\boldsymbol{{give}}\:\boldsymbol{{the}}\:\boldsymbol{{value}}\:\boldsymbol{{of}}\:\boldsymbol{{S}} \\$$
Answered by JDamian last updated on 04/Feb/21
$${S}=\underset{{n}\geqslant\mathrm{1}} {\Sigma}\:\:\frac{\mathrm{1}}{\frac{\boldsymbol{{n}}\left(\boldsymbol{{n}}+\mathrm{1}\right)\left(\mathrm{2}\boldsymbol{{n}}+\mathrm{1}\right)}{\mathrm{6}}} \\$$$$\left(\mathrm{1}\right) \\$$$${a}_{{n}} =\frac{\boldsymbol{{n}}\left(\boldsymbol{{n}}+\mathrm{1}\right)\left(\mathrm{2}\boldsymbol{{n}}+\mathrm{1}\right)}{\mathrm{6}}\:=\:\mathrm{1}^{\mathrm{2}} +\mathrm{2}^{\mathrm{2}} +\mathrm{3}^{\mathrm{2}} +\centerdot\centerdot\centerdot+{n}^{\mathrm{2}} \\$$$$\frac{\mathrm{1}}{{a}_{{n}} }\:=\:\frac{\mathrm{1}}{\mathrm{1}^{\mathrm{2}} +\mathrm{2}^{\mathrm{2}} +\centerdot\centerdot\centerdot+{n}^{\mathrm{2}} }\:<\frac{\mathrm{1}}{{n}^{\mathrm{2}} }\:\:\:\:\forall{n}>\mathrm{1} \\$$$$\underset{{n}\geqslant\mathrm{1}} {\sum}\:\frac{\mathrm{1}}{{a}_{{n}} }\:<\:\underset{{n}\geqslant\mathrm{1}} {\sum}\frac{\mathrm{1}}{{n}^{\mathrm{2}} }=\frac{\pi^{\mathrm{2}} }{\mathrm{6}} \\$$$${S}\:<\:\frac{\pi^{\mathrm{2}} }{\mathrm{6}} \\$$
Answered by Dwaipayan Shikari last updated on 04/Feb/21
$$\underset{{n}\geqslant\mathrm{1}} {\sum}\frac{\mathrm{6}}{{n}\left(\mathrm{2}{n}+\mathrm{1}\right)}−\underset{{n}\geqslant\mathrm{1}} {\sum}\frac{\mathrm{6}}{\left({n}+\mathrm{1}\right)\left(\mathrm{2}{n}+\mathrm{1}\right)} \\$$$$=\underset{{n}=\mathrm{0}} {\overset{\infty} {\sum}}\frac{\mathrm{6}}{\left({n}+\mathrm{1}\right)\left(\mathrm{2}{n}+\mathrm{3}\right)}−\left(\underset{{n}\geqslant\mathrm{0}} {\overset{\infty} {\sum}}\frac{\mathrm{6}}{\left({n}+\mathrm{1}\right)\left(\mathrm{2}{n}+\mathrm{1}\right)}−\underset{{n}\geqslant\mathrm{0}} {\overset{\mathrm{1}} {\sum}}\frac{\mathrm{6}}{\left({n}+\mathrm{1}\right)\left(\mathrm{2}{n}+\mathrm{1}\right)}\right) \\$$$$=\mathrm{6}\left(\psi\left(\frac{\mathrm{3}}{\mathrm{2}}\right)+\psi\left(\frac{\mathrm{1}}{\mathrm{2}}\right)\right)+\mathrm{6} \\$$$$=\mathrm{6}\left(\mathrm{2}−\mathrm{4}{log}\left(\mathrm{2}\right)\right)+\mathrm{6}=\mathrm{6}\left(\mathrm{3}−\mathrm{4}{log}\left(\mathrm{2}\right)\right)\:\:\:\psi\left(\frac{\mathrm{3}}{\mathrm{2}}\right)=\mathrm{2}−\mathrm{2}{log}\left(\mathrm{2}\right)\:\:\psi\left(\frac{\mathrm{1}}{\mathrm{2}}\right)=−\mathrm{2}{log}\left(\mathrm{2}\right) \\$$$$\\$$
Answered by mathmax by abdo last updated on 04/Feb/21
$$\left.\mathrm{1}\right)\:\mathrm{we}\:\mathrm{have}\:\frac{\mathrm{6}}{\mathrm{n}\left(\mathrm{n}+\mathrm{1}\right)\left(\mathrm{2n}+\mathrm{1}\right)}\sim\frac{\mathrm{6}}{\mathrm{2n}^{\mathrm{3}} }=\frac{\mathrm{3}}{\mathrm{n}^{\mathrm{3}} }\mathrm{and}\:\Sigma\:\frac{\mathrm{3}}{\mathrm{n}^{\mathrm{3}} }\mathrm{cv}\:\Rightarrow\mathrm{S}\:\mathrm{cv} \\$$$$\left.\mathrm{2}\right)\frac{\mathrm{S}}{\mathrm{6}}=\mathrm{lim}_{\mathrm{n}\rightarrow+\infty} \mathrm{w}_{\mathrm{n}} \:\mathrm{with}\:\mathrm{w}_{\mathrm{n}} =\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}} \:\frac{\mathrm{1}}{\mathrm{k}\left(\mathrm{k}+\mathrm{1}\right)\left(\mathrm{2k}+\mathrm{1}\right)} \\$$$$\mathrm{let}\:\mathrm{decompose}\:\mathrm{F}\left(\mathrm{x}\right)=\frac{\mathrm{1}}{\mathrm{x}\left(\mathrm{x}+\mathrm{1}\right)\left(\mathrm{2x}+\mathrm{1}\right)}\:,\mathrm{F}\left(\mathrm{x}\right)=\frac{\mathrm{a}}{\mathrm{x}}+\frac{\mathrm{b}}{\mathrm{x}+\mathrm{1}}+\frac{\mathrm{c}}{\mathrm{2x}+\mathrm{1}} \\$$$$\mathrm{a}=\mathrm{1}\:,\mathrm{b}\:=\frac{\mathrm{1}}{\left(−\mathrm{1}\right)\left(−\mathrm{1}\right)}=\mathrm{1}\:,\mathrm{c}\:=\frac{\mathrm{1}}{\left(−\frac{\mathrm{1}}{\mathrm{2}}\right)\frac{\mathrm{1}}{\mathrm{2}}}\:=−\mathrm{4}\:\Rightarrow\mathrm{F}\left(\mathrm{x}\right)=\frac{\mathrm{1}}{\mathrm{x}}+\frac{\mathrm{1}}{\mathrm{x}+\mathrm{1}}−\frac{\mathrm{4}}{\mathrm{2x}+\mathrm{1}} \\$$$$\mathrm{w}_{\mathrm{n}} =\sum_{\mathrm{k}^{} =\mathrm{1}} ^{\mathrm{n}} \frac{\mathrm{1}}{\mathrm{k}}+\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}} \:\frac{\mathrm{1}}{\mathrm{k}+\mathrm{1}}−\mathrm{4}\:\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}} \:\frac{\mathrm{1}}{\mathrm{2k}+\mathrm{1}}\:\mathrm{but} \\$$$$\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}} \:\frac{\mathrm{1}}{\mathrm{k}}=\mathrm{H}_{\mathrm{n}} \sim\mathrm{log}\left(\mathrm{n}\right)+\gamma \\$$$$\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}} \:\frac{\mathrm{1}}{\mathrm{k}+\mathrm{1}}\:=\sum_{\mathrm{k}=\mathrm{2}} ^{\mathrm{n}+\mathrm{1}} \:\frac{\mathrm{1}}{\mathrm{k}}\:=\mathrm{H}_{\mathrm{n}+\mathrm{1}} −\mathrm{1}\:\sim\mathrm{log}\left(\mathrm{n}+\mathrm{1}\right)+\gamma−\mathrm{1} \\$$$$\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}} \:\frac{\mathrm{1}}{\mathrm{2k}+\mathrm{1}}\:=\frac{\mathrm{1}}{\mathrm{3}}+\frac{\mathrm{1}}{\mathrm{5}}+…+\frac{\mathrm{1}}{\mathrm{2n}+\mathrm{1}}\:=\mathrm{1}+\frac{\mathrm{1}}{\mathrm{2}}+\frac{\mathrm{1}}{\mathrm{3}}+….+\frac{\mathrm{1}}{\mathrm{2n}}+\frac{\mathrm{1}}{\mathrm{2n}+\mathrm{1}} \\$$$$−\mathrm{1}−\frac{\mathrm{1}}{\mathrm{2}}−\frac{\mathrm{1}}{\mathrm{4}}−….−\frac{\mathrm{1}}{\mathrm{2n}}=\mathrm{H}_{\mathrm{2n}+\mathrm{1}} −\frac{\mathrm{1}}{\mathrm{2}}\mathrm{H}_{\mathrm{n}} −\mathrm{1}\sim\mathrm{log}\left(\mathrm{2n}+\mathrm{1}\right)+\gamma \\$$$$−\frac{\mathrm{1}}{\mathrm{2}}\left(\mathrm{log}\left(\mathrm{n}\right)+\gamma\right)−\mathrm{1}\:=\mathrm{log}\left(\mathrm{2n}+\mathrm{1}\right)−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{log}\left(\mathrm{n}\right)+\frac{\gamma}{\mathrm{2}}−\mathrm{1}\:\Rightarrow \\$$$$−\mathrm{4}\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}} \:\frac{\mathrm{1}}{\mathrm{2k}+\mathrm{1}}\sim−\mathrm{4log}\left(\mathrm{2n}+\mathrm{1}\right)+\mathrm{2logn}−\mathrm{2}\gamma+\mathrm{4}\:\Rightarrow \\$$$$\mathrm{W}_{\mathrm{n}} \sim\mathrm{log}\left(\mathrm{n}\right)+\gamma+\mathrm{log}\left(\mathrm{n}+\mathrm{1}\right)+\gamma−\mathrm{1}\:−\mathrm{4log}\left(\mathrm{2n}+\mathrm{1}\right)+\mathrm{2log}\left(\mathrm{n}\right)−\mathrm{2}\gamma\:+\mathrm{4}\:\Rightarrow \\$$$$\mathrm{W}_{\mathrm{n}} \sim\mathrm{log}\left(\mathrm{n}^{\mathrm{3}} \right)+\mathrm{log}\left(\mathrm{n}+\mathrm{1}\right)−\mathrm{4log}\left(\mathrm{2n}+\mathrm{1}\right)+\mathrm{3}\:\Rightarrow \\$$$$\mathrm{W}_{\mathrm{n}} \sim\mathrm{log}\left(\frac{\mathrm{n}^{\mathrm{4}} \:+\mathrm{n}^{\mathrm{3}} }{\left(\mathrm{2n}+\mathrm{1}\right)^{\mathrm{4}} }\right)+\mathrm{3}\:\Rightarrow\mathrm{W}_{\mathrm{n}} \rightarrow\mathrm{3}−\mathrm{4log}\left(\mathrm{2}\right)\:\Rightarrow \\$$$$\mathrm{S}\:=\mathrm{6}\:\mathrm{W}_{\infty} =\mathrm{6}\left(\mathrm{3}−\mathrm{4log}\left(\mathrm{2}\right)\right) \\$$$$\\$$
Commented by pticantor last updated on 08/Feb/21
$$\boldsymbol{{thank}}\:\boldsymbol{{you}}\:\boldsymbol{{too}}\:\boldsymbol{{much}} \\$$